49.3k views
2 votes
I am attaching the question

I am attaching the question-example-1
User SelvaS
by
5.8k points

1 Answer

3 votes

Answer:

r =
(120t)/(120-t)

Explanation:

Multiply both sides by r + 120.

t (r + 120) = 120r

Expand.

tr + 120t = 120r

Subtract tr from both sides.

120t = 120r - tr

Factor out the common term r.

120t = r (120-t)

Divide both sides by 120 - t.


(120t)/(120-t) = r

Finally, switch r to the left side and you get your answer.

//also, sorry for answering late.. my wifi is poopy//

User Justify
by
5.2k points